Readmission Rates and Their Impact on Hospital Financial Performance: A Study of Washington Hospitals - Soumya Upadhyay PhD; Amber L. Stephenson PhD; Dean G. Smith PhD (SAGE Publishing, 2019)
This longitudinal study examines whether readmission rates, made transparent through Hospital Compare, affect hospital financial performance by examining 98 hospitals in the State of Washington from 2012 to 2014. Readmission rates for acute myocardial infarction (AMI), pneumonia (PN), and heart failure (HF) were examined against operating revenues per patient, operating expenses per patient, and operating margin. Using hospital-level fixed effects regression on 276 hospital year observations, the analysis indicated that a reduction in AMI readmission rates is related with increased operating revenues as expenses associated with costly treatments related with unnecessary readmissions are avoided. Additionally, reducing readmission rates is related with an increase in operating expenses. As a net effect, increased PN readmission rates may show marginal increase in operating margin because of the higher operating revenues due to readmissions. However, as readmissions continue to happen, a gradual increase in expenses due to greater use of resources may lead to decreased profitability.